Miracles - Chan, Jackie; Wong, Arthur; Mui, Anita; Chow, Billy (Hong Kong Legends, 1993)
Jackie Chan is one of those people who is instantly likeable onscreen no matter what he's doing. His comedic timing is impeccable, but so are his fight sequences. Here, as always, he works without stunt doubles, and yes, we do get to see his traditional injury outtakes during the closing credits. But in this film, moreso than many of his others, Chan gets to be an actor, and proves that he has talent in more than just martial arts. He is the center that holds this remarkable film together, and it all ends in a wonderful penultimate scene that should bring tears to your eyes. It did mine, and when a film can manage to make me care, laugh and cry all in the same two plus hours, it's definitely a winner. [www.filmmonthly.com]
Keywords: DVD-Video